2000
DOI: 10.1016/s0378-1097(00)00345-1
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel formation by N-terminal domain: a common feature of OprFs of Pseudomonas and OmpA of Escherichia coli

Abstract: The proteolytic fragments of OprFs of Pseudomonas aeruginosa and Pseudomonas fluorescens were identified, respectively, as the first 175 and 177 amino acids from the N-terminal domain. They induced ion channels after reincorporation into planar lipid bilayers (85 and 75 pS, respectively, in 1 M NaCl). A similar conductance value (72 pS) was found for the eight L-strand OmpA N-terminal domain (OmpA 171 ) of Escherichia coli. We conclude that the N-terminal domain of OprFs is sufficient to induce ion channels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
4
30
2
Order By: Relevance
“…In any case, we did not observe the diffusion of the smallest organic solutes we could test in the liposome swelling assay (e.g. glycine) through the N-terminal domain of OprF, and we suggest that the N-terminal eight-stranded ␤-barrel domain should be thought of as a completely closed channel despite the suggestions from other laboratories (8,28) as well as from a computer modeling study of its homolog OmpA (30). In conclusion, our results as well as results from other laboratories suggest strongly that the large channel is produced by the folding of the entire OprF sequence to produce a ␤-barrel of many strands, certainly more than eight and perhaps close to 16, that are found in classical porins (see Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…In any case, we did not observe the diffusion of the smallest organic solutes we could test in the liposome swelling assay (e.g. glycine) through the N-terminal domain of OprF, and we suggest that the N-terminal eight-stranded ␤-barrel domain should be thought of as a completely closed channel despite the suggestions from other laboratories (8,28) as well as from a computer modeling study of its homolog OmpA (30). In conclusion, our results as well as results from other laboratories suggest strongly that the large channel is produced by the folding of the entire OprF sequence to produce a ␤-barrel of many strands, certainly more than eight and perhaps close to 16, that are found in classical porins (see Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…A survey of the literature shows that barrels with fewer or with more ␤-strands than the predicted 10 for HMW1B form pores with smaller conductance values than what we report here. For example, the conductance of the eight ␤-stranded N-terminal domain barrel of OmpA is ϳ110 pS in 1 M KCl (44). The conductance appears to increase for pores containing a larger number of ␤ strands (for example, 800 pS for the monomeric OmpG (14 strands) (45) or 1200 pS for FhaC (16 strands) (18)), but one has to exercise caution because the conductance is not only determined by the pore diameter but also by the charges and the electric field within the pore as well as by the access resistance of the pore (46).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an operon formed by a hypothetical protein BT2437 from Bacteroides thetaiotaomicron VPI-5482 was found that codes for a putative lipoprotein (Chang et al, 1999). Proteins from this family are always associated with channelforming eight-stranded beta-barrel proteins from the OprF family (Saint et al, 2000) (Figure 5c). The list of hypothetical proteins and predicted functions can be found in Supplementary Table S11.…”
Section: Analysis Of Unknown Hypothetical Proteinsmentioning
confidence: 99%